PENGUATAN SDGs PESANTREN MELALUI PENGELOLAAN SAMPAH BERBASIS PARTICIPATORY ACTION RESEARCH (PAR) - Sufiyanto, Mohammad Imam; Anwar, Mohammad Muhlis; Khairunisa, Khairunisa (Universitas Mataram, 2024)
Waste is a commodity that has always been a threat to all groups, including those in Islamic boarding schools, so steps are needed to find solutions to decompose waste that always appears every day to have economic value. Pesantren which accommodates thousands of students will certainly produce waste that spits every day. This will also cause more problems due to accumulated garbage, causing various kinds of diseases and floods in the rainy season. The purpose of the service to be achieved is to reduce the risk of garbage accumulation in Islamic boarding schools in order to reduce the accumulation of waste and make waste into economical goods. This problem-solving stage is carried out using the Participatory Action Research (PAR) approach method to find bright spots for relevant solutions needed to reduce waste accumulation. The conclusion is to maximize the provision of materials, demonstrations, and practices to be able to reduce the waste generated every day. As a result of the discussion process with service partners, it was decided that what was needed by the pesantren was training and insightful knowledge about waste management so that it was economically valuable and demonstration of procedures for making fertilizer from pesantren public kitchen waste. In conclusion, training and training show that the students are very enthusiastic in receiving material.